Monetary Policy Rules Based on Real-Time Data - Orphanides, Athanasios (American Economic Review, 2001)
This paper examines the magnitude of informational problems associated with the implementation and interpretation of simple monetary policy rules. Using Taylor's rule as an example, I demonstrate that real-time policy recommendations differ considerably from those obtained with ex post revised data. Further, estimated policy reaction functions based on ex post revised data provide misleading descriptions of historical policy and obscure the behavior suggested by information available to the Federal Reserve in real time. These results indicate that reliance on the information actually available to policy makers in real time is essential for the analysis of monetary policy rules. (JEL E52, E58)